2013
DOI: 10.1038/bjc.2013.174
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of IL-6 and IL-1β can predict the efficacy of gemcitabine in patients with advanced pancreatic cancer

Abstract: Background:With this study, we sought to characterise the impact of pro-inflammatory cytokines on the outcomes of gemcitabine monotherapy (GEM) in patients with pancreatic cancer (PC).Methods:Treatment-naive patients with advanced PC and no obvious infections were eligible for enrolment. All of the patients were scheduled to undergo systemic chemotherapy. Serum pro-inflammatory cytokines were measured using an electro-chemiluminescence assay method before chemotherapy. High cytokine levels were defined as valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 34 publications
8
98
2
6
Order By: Relevance
“…In addition to confirming our hypothesis, we observed that LIF titration in serum from PDA patients could have other uses. Indeed, as already reported for IL-6 and IL-11, cytokine serum levels are valuable diagnostic and prognostic tools (47)(48)(49) suggests that the combined detection of LIF and CA19.9 could be greater than CA19.9 alone in the diagnosis of PDA. Finally, LIF titration in serum of PDA patients has a real potent value as a stratifying biomarker of PDA in order to classify PDA patients regarding their possible responsiveness to JAK/STAT targeting agent as Ruxolitinib.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to confirming our hypothesis, we observed that LIF titration in serum from PDA patients could have other uses. Indeed, as already reported for IL-6 and IL-11, cytokine serum levels are valuable diagnostic and prognostic tools (47)(48)(49) suggests that the combined detection of LIF and CA19.9 could be greater than CA19.9 alone in the diagnosis of PDA. Finally, LIF titration in serum of PDA patients has a real potent value as a stratifying biomarker of PDA in order to classify PDA patients regarding their possible responsiveness to JAK/STAT targeting agent as Ruxolitinib.…”
Section: Discussionmentioning
confidence: 81%
“…This cytokine plays a key role in the early growth, maintenance, and metastasis of PDAC tumors (27, 28). Previous studies in either mixed cohorts of patients with resectable and unresectable disease (36, 37) or in those undergoing gemcitabine based therapy (38) have found a negative correlation between IL-6 and clinical outcome. In agreement with these reports, our study found that IL-6 plasma levels in treatment naïve patients were significantly negatively associated OS.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, improving the immune status of cancer patients is required for effective cancer immunotherapies. Prospective and retrospective studies have shown that serum IL-6 levels are related to tumor stage and size, metastasis, survival of colon cancer patients [19], chemotherapy efficacy for advanced pancreatic cancer [20], advanced stage and metastasis-related morbidity of breast cancer [21], and the efficacy of personalized peptide vaccination for advanced biliary tract cancer [22]. Results from these studies suggest that IL-6 levels in cancer are not simply useful as promising prognostic biomarkers, but are also related to tumorigenesis and anti-tumor immune responses.…”
Section: Discussionmentioning
confidence: 99%